Doublecortin‐like kinase 1 is a therapeutic target in squamous cell carcinoma. Issue 2 (11th October 2022) - Standing, David; Arnold, Levi; Dandawate, Prasad; Ottemann, Brendan; Snyder, Vusala; Ponnurangam, Sivapriya; Sayed, Afreen; Subramaniam, Dharmalingam; Srinivasan, Pugazhendhi; Choudhury, Sonali; New, Jacob; Kwatra, Deep; et al.
Abstract: Doublecortin like kinase 1 (DCLK1) plays a crucial role in several cancers including colon and pancreatic adenocarcinomas. However, its role in squamous cell carcinoma (SCC) remains unknown. To this end, we examined DCLK1 expression in head and neck SCC (HNSCC) and anal SCC (ASCC). We found that DCLK1 is elevated in patient SCC tissue, which correlated with cancer progression and poorer overall survival. Furthermore, DCLK1 expression is significantly elevated in human papilloma virus negative HNSCC, which are typically aggressive with poor responses to therapy. To understand the role of DCLK1 in tumorigenesis, we used specific shRNA to suppress DCLK1 expression. This significantly reduced tumor growth, spheroid formation, and migration of HNSCC cancer cells. To further the translational relevance of our studies, we sought to identify a selective DCLK1 inhibitor. Current attempts to target DCLK1 using pharmacologic approaches have relied on nonspecific suppression of DCLK1 kinase activity. Here, we demonstrate that DiFiD (3, 5‐bis [2, 4‐difluorobenzylidene]−4‐piperidone) binds to DCLK1 with high selectivity. Moreover, DiFiD mediated suppression of DCLK1 led to G2/M arrest and apoptosis and significantly suppressed tumor growth of HNSCC xenografts and ASCC patient derived xenografts, supporting that DCLK1 is critical for SCC growth.